A Quality Mobility Program Reduces Elderly Social Isolation. Issue 1 (2nd January 2021) - Sen, Keya; Prybutok, Gayle
ABSTRACT: Community programs on physical activity can alleviate social isolation among the older population. This case study explores the perceptions of seniors 50 years and above who participate in 'Seniors in Motion', an innovative, community based senior physical exercise facility located in north Texas and evaluates the program's worth in fostering social interaction among the participants. A qualitative research design based on over 12 hours of semi-structured interviews with 15 participants at the facility assesses program effectiveness in reducing isolation. When clinical professionals supervise exercise in a safe and age-friendly environment, it reduces the unnecessary use of health care services with a greater emphasis on safety, injury prevention and low out-of-pocket costs. Such a unique care delivery structure fosters sustained relationships that improve the quality of life and establish a new social support system. It builds trust among participants, ensures quality of service delivery and productive physical and social outcomes. Interview themes highlight the importance of interaction and support between facility staff and participants and between participants and other participants, which leads to increased motivation for physical activity and social interactions. Results suggest that a combination of physical activity and proximity to the senior exercise center improves social engagement.